Análise da potencialidade de geração de energia elétrica a partir do biogás de aterro sanitário na cidade de Itapeva/SP - Rossini, Matheus Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The increase in population and in consumption of goods and services, stimulated by technological innovations, directly influences on generation of municipal solid waste (MSW) and the use of resources for generating energy, increasing greenhouse gas emissions, as well as other problems associated with MSW. Even with the establishment of the National Policy on Solid Waste, the disposal of MSW is classified as inadequate according to CETESB, not only in Itapeva/SP but in most of the municipalities in Brazil. Thus, the study consisted in applying USEPA's (1998 and 2005) and World Bank (Scholl Canyon) biogas generation models to estimate the methane production from Itapeva/SP MSW. The input parameters were the same for each model. The values obtained for the methane generation potential (L0) and for the methane (k) generation rate were 99.33 m3CH4 / ton. RSU and 0.06, respectively. It was considered 9 different cases in relation to the time of reception of residues in the landfill and the increase in the MSW generation rate. For each of the 9 cases, the total production of CH4 (m3), the average amount of electric energy available per year and the percentage of Itapeva's population that could benefit from such energy were obtained. For the more conservative case (case 1), it would be possible to benefit 0.46% of the population, while 1.55% would benefit from the more optimistic forecast (case 9). In addition, special cases were applied to obtain the amount of RSU needed to benefit 50% of the population. Finally, the portion of the benefited population was obtained in each of the initial cases, considering the RSU generation rate as being the sum of Itapeva's and some of the neighboring munipalities' RSU generation rate. In this case, the amount of available energy and the share of the beneficiary population were increased. Although some assumptions were conservative and can be better refined, the results...

O aumento da população e do consumo de bens e serviços, estimulado pelas inovações tecnológicas, impacta diretamente a geração de resíduos sólidos urbanos (RSU) e a utilização de recursos para geração de energia, aumentando as emissões de gases do efeito estufa, além de outros problemas associados aos RSU. Mesmo com o estabelecimento da Política Nacional dos Resíduos Sólidos, a disposição dos RSU na cidade de Itapeva/SP é classificada como inadequada segundo a CETESB, assim como grande parte dos municípios no Brasil. Assim, o estudo consistiu na aplicação dos modelos de previsão de geração de biogás da USEPA (1998 e 2005) e do Banco Mundial (Scholl Canyon), para estimar a produção de metano proveniente dos RSU de Itapeva/SP. Os parâmetros de entrada foram os mesmos para cada modelo. Os valores obtidos para o potencial de geração de metano (L0) e para a taxa de geração de metano (k) foram 99,33 m3CH4/ton. RSU e 0,06, respectivamente. Foram aplicados 9 casos distintos com relação ao tempo de recepção de resíduos no aterro e ao incremento na taxa de geração de RSU. Para cada um dos 9 casos foi obtida a produção total de CH4 (m3), a quantidade média de energia elétrica disponível por ano e a parcela da população atual de Itapeva/SP que poderia ser beneficiada com tal energia. Para o caso mais conservador (caso 1), seria possível beneficiar 0,46% da população, enquanto 1,55% seria beneficiada pela previsão mais otimista (caso 9). Adicionalmente, foram aplicados casos especiais para a obter a quantidade de RSU necessária para beneficiar 50% da população. Por fim, obteve-se a parcela da população beneficiada em cada um dos casos iniciais, considerando a taxa de geração de RSU como sendo o acumulado entre Itapeva/SP e alguns municípios vizinhos. Para este caso, aumentou-se a quantidade de energia disponível e a parcela da população beneficiada. No geral, foram adotadas premissas...
Keywords: Energia - Fontes alternativas; Energia elétrica; Biogas; Aterro sanitário; Resíduos sólidos; Sustentabilidade; Renewable energy sources